Efek Aromaterapi Minyak Esensial terhadap Nyeri pada Pasien Pasca Pembedahan Gastrointestinal - Sianturi, Natallina; Dahlia, Debie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to show the effectiveness of essential oil aromatherapy for pain compared with standard intervention measures in patients after gastrointestinal surgery. The research method used is a systematic review through databases and electronic websites, namely Pubmed, Science Direct, ProQuest, Embase and Sage Journals. The results of the study showed that from 5 research articles, data was obtained that giving Aromatherapy essential oils was proven to reduce pain after gastrointestinal surgical procedures, including lavender oil, geranium oil, mixing lavender, ylang-ylang, marjoram and neroli oils as well as sweet orange and rose types. Silk cloth. Conclusion: The addition of aromatherapy to standard therapy significantly reduces the severity of postoperative pain compared to standard therapy with or without placebo. Keywords: aromatherapy essential oils, pains, gastrointestinal surgery